2017
DOI: 10.1209/0295-5075/117/57009
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-mediated dynamic screening in the integer quantum Hall effect regime

Abstract: Quantum Hall effects PACS 73.43.Nq -Quantum phase transitions PACS 73.23.-b -Electronic transport in mesoscopic systemsAbstract -We study many-body interaction effects in the spatially-resolved filling factor (ν) distribution for higher Landau levels (LLs) via self-consistent Hartree-Fock simulations in the integer quantum Hall (IQH) regime. Our results indicate a strong, interaction-induced tendency to avoid the simultaneous existence of partially filled spin-up and spin-down LLs. Rather, we find that such pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
3
14
0
Order By: Relevance
“…2 of Ref. 17) we observe strong resistance fluctuations in both, as also expected for QH structures of mesoscopic size. 36 In Fig.…”
Section: A Transportsupporting
confidence: 85%
See 2 more Smart Citations
“…2 of Ref. 17) we observe strong resistance fluctuations in both, as also expected for QH structures of mesoscopic size. 36 In Fig.…”
Section: A Transportsupporting
confidence: 85%
“…In Ref. 17, we have shown that the B-dependences of the longitudinal resistance, R xx , and the Hall resistance, R xy , exhibit the expected R xx peaks in the transition regime between QH plateaus and Hall plateaus at zero R xx . In the transition regime between plateaus (cp.…”
Section: A Transportmentioning
confidence: 79%
See 1 more Smart Citation
“…In this paper, we focus on the theoretical foundations of the scaling theory and the CSG theory, that have been successfully justified many times [7][8][9][10][11][12][13][14] although they seem to rest on conflicting theoretical foundations 15 . In recent papers we argue that both pictures can only coexist on the basis of many body interactions [15][16][17][18] . Werner et al have shown that many body interactions are almost completely captured within a system of size 1000 × 1000nm 15 .…”
mentioning
confidence: 99%
“…We use a Hartree-Fock approach as explained in previous work [16][17][18][19] , where we have shown that the keymechanism dictating the electron system is a Hund's rule behaviour for the occupation of the spin-split LLs. The resulting g-factor enhancement appears as an almost local quantity depending on the local filling factor.…”
mentioning
confidence: 99%